2006
DOI: 10.1529/biophysj.105.077107
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Fluid-Ordered/Fluid-Disordered Phase Coexistence in Ceramide/POPC Mixtures Containing Cholesterol

Abstract: The effect of temperature on the lateral structure of lipid bilayers composed of porcine brain ceramide and 1-palmitoyl 2-oleoyl-phosphatidylcholine (POPC), with and without addition of cholesterol, were studied using differential scanning calorimetry, Fourier transformed infrared spectroscopy, atomic force microscopy, and confocal/two-photon excitation fluorescence microscopy (which included LAURDAN generalized polarization function images). A broad gel/fluid phase coexistence temperature regime, characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
107
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 50 publications
(98 reference statements)
18
107
0
Order By: Relevance
“…The importance of ceramide in modulating membrane physical properties and biological function has prompted a number of studies of ceramide incorporation in model membranes. Several recent investigations have examined the effects of ceramide incorporation on coexisting ordered and fluid domains in phase separated binary and ternary lipid mixtures that are used to model membrane rafts Fidorra et al, 2006;Silva et al, 2007;Sot et al, 2006Sot et al, , 2008. This work has demonstrated that ceramide leads to increased membrane heterogeneity and that its effects depend on the membrane composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of ceramide in modulating membrane physical properties and biological function has prompted a number of studies of ceramide incorporation in model membranes. Several recent investigations have examined the effects of ceramide incorporation on coexisting ordered and fluid domains in phase separated binary and ternary lipid mixtures that are used to model membrane rafts Fidorra et al, 2006;Silva et al, 2007;Sot et al, 2006Sot et al, , 2008. This work has demonstrated that ceramide leads to increased membrane heterogeneity and that its effects depend on the membrane composition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, treating phosphatidylcholine/SM vesicles with SMase produced ceramide patches that coalesced into larger domains and then formed vesicles (Holopainen et al, 2000;Nurminen et al, 2002). Several other studies have provided evidence for ceramide-enriched domains in monolayers (Fanani et al, 2002;Hartel et al, 2005), in fluid phospholipid vesicles (Taniguchi et al, 2006) and in giant vesicles prepared from SM/ceramide or ceramide/POPC/cholesterol mixtures (Fidorra et al, 2006;Sot et al, 2006). These studies in monolayers and vesicles indicate that enzymatic generation of ceramide leads to more complex changes in membrane morphology than does direct ceramide incorporation in the same lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary GUV imaging techniques, such as fluorescence lifetime imaging microscopy (FLIM) or the use of environmental probes such as Laurdan can also be useful in identifying phases. [55][56][57] Complementary techniques using geometries other than GUVs (e.g. nuclear magnetic resonance or electron paramagnetic resonance on multilamellar vesicles) produce excellent determinations of the lipid ratios and temperatures at which all three phases coexist.…”
Section: Fluorescence Microscopy To Identify Coexisting Gel and Liquimentioning
confidence: 99%
“…GUVs were prepared using the electroformation method developed by Angelova et al ( 19 ), using a specialized chamber supplied by L. A. Bagatolli (Odense, Denmark) that allows direct visualization under the microscope ( 53 ). Stock solutions of lipids (0.2 mg/ml total lipid containing 0.2 mol% DiI) were prepared in a chloroform-methanol (9:1, v/v) solution.…”
Section: Guv Preparation and Fl Uorescence Microscopymentioning
confidence: 99%